Influence of different drug delivery methods for Endostar combined with a gemcitabine/cisplatin regimen in locally advanced or metastatic lung squamous cell carcinoma: A retrospective observational study. Issue 32 (August 2018) - Yao, Difei; Shen, Hong; Huang, Jianjin; Yuan, Ying; Dai, Haibin
Abstract : Abstract: Continuous endovenous administration of Endostar (CE) gradually replaced drip intravenous administration of Endostar (DE) in lung squamous cell carcinoma (SCC) treatment presently, but the efficacy and safety of CE and DE which is better in advanced lung SCC are yet unclear. To evaluate the feasibility of CE as an alternative to DE with gemcitabine/cisplatin (GP) chemotherapy. Data were collected from patients admitted with locally advanced or metastatic lung SCC from January 2011 to April 2015, including the patients' characteristics, the therapeutic regimen, the treatment effectiveness, and toxicity. There are 71 patients with pathologically confirmed lung SCC retrospectively assigned to a treatment (CE) group of 48 patients and a control (DE) group of 23 patients. The response of each tumor to the therapy was assessed every 2 cycles by a chest and upper abdomen computed tomography for the comparison of curative effects and adverse reactions. Compared with the DE group, the response rate and disease control rate were noninferior in the CE group. The median progression-free survival and overall survival in the CE and DE groups were no significantly difference (5.5 vs 5.5 months, P  = .141; 22.9 vs 14.3 months, P  = .053). Increased progression-free survival (PFS) for patients in CE group was observed across 3 subgroups analyzed. There was a 35.7% reduction in the total dose of Endostar per cycle in the CE group compared with that in the DE group. Thus, in combination with GP chemotherapy, CE could be a suitable alternative to DE in locally advanced or metastatic SCC patients, resulting in less hemoptysis, less treatment time, and lower costs.